PENGEMBANGAN PEMBELAJARAN USU>L AL-FIQH BERBASIS KOMPETENSI PADA MADRASAH ALIYAH KEAGAMAAN DI PONOROGO - Basuki Basuki (IAIN Ponorogo, 2018)
Abstract: This article aims to explain the objectives, materials, strategies, and evaluations that have been formulated from usu>l al-fiqh learning in Religious Madrasah Aliyah (MAK) in Islamic boarding schools in Ponorogo district, especially at MAK Pondok